Phenomenological Barriers to Cyber Extension Adoption among Agricultural Extension Workers - Sabaruddin Sabaruddin; Tuti Bahfiarti; Farid (LONTAR: Jurnal Ilmu Komunikasi, 2026)
This study explored the phenomenological barriers experienced by agricultural extension workers in adopting the Cyber Extension platform in Pangkajene and Islands Regency. Using a phenomenological approach, data were collected through in-depth interviews, participatory observation, and documentation, then analyzed thematically. Four  main themes emerged: (1) infrastructure limitations, especially unstable and uneven internet access in mountainous and island regions, disrupted  the delivery of digital  extension services; (2) low digital literacy skills, particularly among senior extension workers, was exacerbated by the lack of regular  and comprehensive  technology training; (3) resistance to technological change was evident in skepticism toward digital platforms, with a preference for conventional, face to face  method that were perceived  as more effective  for farmer engagement; and (4) weak policy support and insufficient  inter-agency coordination resulted in limited budget allocation, inadequate facilities, and fragmented training programs. These structural gaps forced extension workers to rely on personal resources  to sustain implementation. The findings indicated that digital transformation in  agricultural extension requires not only reliable infrastructure but also targeted capacity building, cultural readiness, and strong institutional backing. A holistic, context-sensitive strategy is essential to optimize Cyber Extension adoption, particularly in areas facing geographical challenges.